DAMPAK DEFISIT ANGGARAN PENDAPATAN BELANJA NEGARA DAN INVESTASI ASING PADA INDUSTRI PENGOLAHAN NON MIGAS TERHADAP NERACA PERDAGANGAN - Anita, Darma; Aulia, Ando Fahda; ', Syapsan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the impact of budget deficits and governmentspending and income of foreign investment in non-oil industrial processing on the trade balance. This study uses secondary file obtained from BPS and Ministry of Finance. This research was conducted nationally namely Indonesia in the period 2000 to 2014.This study uses a quantitative method, and analyzed using analytical tools error correction model using a computer application program Eviews version 7. The study consists of three independent variables (the budget deficit, foreign investment in the manufacturing and processing industry non-oil GDP) and one the dependent variable (Indonesia's trade balance).The results obtained are in the long-term budget deficit, and foreign investment in the processing industry have a significant effect on the trade balance of Indonesia. However, non-oil GDP of processing industry was not significant. However, in the short-term budget deficit has no significant effect. Meanwhile, foreign investment in the processing and processing industry non-oil GDP has significant impact on Indonesia's trade balance. In this study showed, too, that the budget deficit had a negative impact on the trade balance of Indonesia. Meanwhile, foreign investment in the processing and processing industry of non-oil GDP a positive impact on Indonesia's trade balance.Keywords: the budget deficit, foreign investment,GDP, Indonesia's trade balance